Bauran Promosi Produk Fashion Lifestyle Otomotif - Muhammad Zahid Waliullah; Anne Ratnasari (Bandung Conference Series: Communication Management, 2024)
Abstract. In this era of globalization, the fashion business has experienced significant growth, one of which is in the city of Bandung. Pickers Store is one of the businesses in the fashion sector in the city of Bandung, which is unique in that most of the products and product concepts are always identical to automotive, especially classic vehicles. The purpose of this study is to find out how the content of fashion product advertising messages on Instagram, the use of product sales promotion carried out by pickers and find out why the BBQ RIDE event is a mainstay in promoting Pickers fashion products on Instagram @pickerstore. So this research is expected to provide more knowledge for other researchers regarding the Promotion Mix of Fashion Products through Instagram, and it is hoped that there will be more development for Pickers Store regarding the presentation of advertisements and content as promotional activities for its products. This research uses qualitative research methods with a case study approach. The data collection techniques used are observation, interviews, documentation, and literature study. The subjects of this research are Pickers Store Owner, Pickers Store Social Media Marketing. This study reveals the success of Pickers Store, through Instagram @pickerstore, in implementing a promotional mix for automotive lifestyle fashion products. With comprehensive advertising content, Pickers Store has succeeded in building emotional relationships with consumers, creating product meanings through automotive symbols. Usage Abstrak. Di era globalisasi ini bisnis fashion mengalami pertumbuhan yang sangat signifikan, salah satunya di kota Bandung. Pickers Store merupakan salah satu usaha dibidang fashion di kota Bandung, yang memiliki keunikan dari sebagian besar seluruh produk dan konsep produk selalu identik dengan otomotif, khususnya kendaraan klasik. Tujuan penelitian ini untuk mengetetahui bagaimana isi pesan iklan produk fashion di instagram, penggunaan sales promotion produk yang dilakukan oleh pickers dan meingeitahuii mengapa event BBQ RIDE menjadi andalan dalam mempromosikan produk fashion Pickers di Instagram @pickerstore. Maka penelitian ini diharapkan dapat memberikan pengetahuan yang lebih bagi peneliti lain mengenai Bauran Promosi Produk Fashion melalui Instagram, serta diharapkan adanya perkembangan lebih bagi Pickers Store mengenai penyajian iklan dan konten sebagai kegiatan promosi produknya. Penelitian ini menggunakan metode penelitian kualitatif dengan pedekatan studi kasus. Teknik pengumpulan data yang digunakan adalah, observasi, wawancara, dokumentasi, dan studi kepustakaan. Subjek penelitian ini yaitu Owner Pickers Store, Sosial Media Marketing Pickers Store. Penelitian ini mengungkapkan keberhasilan Pickers Store, melalui Instagram @pickerstore, dalam menerapkan bauran promosi produk fashion lifestyle otomotif. Dengan konten iklan yang menyeluruh, Pickers Store berhasil membangun hubungan emosional dengan konsumen, menciptakan makna produk melalui simbol-simbol otomotif. Penggunaan Sales Promotion melalui Instagram dan keberhasilan event BBQ RIDE mendukung efektivitas strategi promosi Pickers Store, menjadikannya merek fashion lifestyle otomotif yang menarik dan berdaya saing.